Accounting for the benefits of technology change: Replacing a zinc-coating process by a water-based organo-metallic coating process. (10th February 2018) - Almeida, C.M.V.B.; Sevegnani, F.; Agostinho, F.; Liu, Gengyuan; Yang, Zhifeng; Coscieme, L.; Giannetti, B.F.
Abstract: Technology change is a well-known strategy used by Cleaner Production (CP) practitioners, and it refers to modifications in the process and/or equipment to increase production efficiency and reduce waste and emissions. These changes can range from small, low-cost options to the replacement of processes that involve large capital investments. The improvements and advantages of the new alternatives must be evaluated in a way to measure and assure its real benefits. This work presents an emergy evaluation of a fasteners manufacturing company planning to replace the zinc-coating process by a water-based organo-metallic coating process. Accounting for the use of resources and the environmental services to dilute the Cr (VI) in the effluent, the study shows that the effluent treatment is efficient and that the emergy invested by the environment to dilute the Cr (VI) released is lower than 0.1% of the emergy used in the coating process. The case study is an example of the application and evaluation of CP options (good operational practices, material and raw material changes, technological modifications, and product change) and is presented to motivate product manufacturers to prioritize environmental performance assessments to their products and services equally as well as to save manufacturers substantial time and efforts during their first attempts to implement CP actions. Highlights: An emergy evaluation of the replace the zinc-coating process by a water-based organo-metallic coating process. The change in the process was motivated by customer requirements. Results motivate product manufacturers to prioritize environmental performance assessments.